The law isn't everything: The impact of legal and non-legal sanctions on motorists' drink driving behaviors. (December 2016) - Freeman, James; Szogi, Elizabeth; Truelove, Verity; Vingilis, Evelyn
Abstract: Introduction: The effectiveness of drink driving countermeasures (such as sanctions) to deter motorists from driving over the legal limit is extremely important when considering the impact the offending behavior has on the community. However, questions remain regarding the extent that both legal and non-legal factors influence drink driving behaviors. This is of particular concern given that both factors are widely used as either sanctioning outcomes or in media campaigns designed to deter drivers (e.g., highlighting the physical risk of crashing). Method: This paper reports on an examination of 1, 253 Queensland motorists' perceptions of legal and non-legal drink driving sanctions and the corresponding deterrent impact of such perceptions on self-reported offending behavior. Participants volunteered to complete either an online or paper version of the questionnaire. Results: Encouragingly, quantitative analysis of the data revealed that participants' perceptions of both legal sanctions (e.g., certainty, severity and swiftness) as well as non-legal sanctions (e.g., fear of social, internal or physical harm) were relatively high, with perceptual certainty being the highest. Despite this, a key theme to emerge from the study was that approximately 25% of the sample admitted to drink driving at some point in time. Multivariate analyses revealed six significant predictors of drink driving, being: males, younger drivers, lower perceptions of the severity of sanctions, and less concern about the social, internal, and physical harms associated with the offense. However, a closer examination of the data revealed that the combined deterrence model was not very accurate at predicting drink driving behaviors (e.g., 21% of variance). Practical applications: A range of non-legal deterrent factors have the potential to reduce the prevalence of drink driving although further research is required to determine how much exposure is required to produce a strong effect. Highlights: The largest proportion of the sample reported high perceptions regarding the certainty, severity and swiftness of sanctions Perceptions of non-legal sanctions such as fear of social, internal and physical harm were also high Approximately one quarter of the sample admitted to drink driving at some point in time Drink drivers were younger males with lower perceptions of sanction severity who were less concerned about the social, internal and physical harm Drink drinking was associated with younger males, lower perceptions of sanction severity as well as non-legal sanctions.